2013
DOI: 10.1088/1748-3182/8/3/036011
|View full text |Cite
|
Sign up to set email alerts
|

A bio-inspired study on tidal energy extraction with flexible flapping wings

Abstract: Previous research on the flexible structure of flapping wings has shown an improved propulsion performance in comparison to rigid wings. However, not much is known about this function in terms of power efficiency modification for flapping wing energy devices. In order to study the role of the flexible wing deformation in the hydrodynamics of flapping wing energy devices, we computationally model the two-dimensional flexible single and twin flapping wings in operation under the energy extraction conditions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 28 publications
0
48
1
Order By: Relevance
“…At a similar Strouhal number, 0.033 in this study versus 0.050 by Wu et al (2015), the mean value of the power coefficient, C p , is 0.144 in this study versus 0.032 for Wu et al This indicates the advantage of the added component due to angular motion induced by the present study. Similarly, at a reduced frequency of 0.048 in the present study versus 0.05 used by Liu et al (2013), the mean value of the power coefficient in the present study is 0.12, compared with that of Liu et al of 0.0625. So in both of these cases, a significant increase in the mean power coefficient is obtained for equivalent measures of Strouhal number and reduced frequency for a rigid wing undergoing the off-chord pitching motion.…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…At a similar Strouhal number, 0.033 in this study versus 0.050 by Wu et al (2015), the mean value of the power coefficient, C p , is 0.144 in this study versus 0.032 for Wu et al This indicates the advantage of the added component due to angular motion induced by the present study. Similarly, at a reduced frequency of 0.048 in the present study versus 0.05 used by Liu et al (2013), the mean value of the power coefficient in the present study is 0.12, compared with that of Liu et al of 0.0625. So in both of these cases, a significant increase in the mean power coefficient is obtained for equivalent measures of Strouhal number and reduced frequency for a rigid wing undergoing the off-chord pitching motion.…”
Section: Resultscontrasting
confidence: 50%
“…On the contrary, the effect of wing flexibility on energy harvesting is not well understood. Liu et al (2013) showed, using 2D computational modeling, that a deforming trailing edge of a wing is beneficial to energy extraction by increasing the instantaneous lift force. On the other hand, a flexible leading edge has the ability to manipulate the phase shift between the instantaneous forces and the wing motion.…”
Section: Introductionmentioning
confidence: 99%
“…8C) to show the influence of wing flexibility on hovering, which demonstrates that aerodynamic performance can be enhanced by wing flexibility. Additionally, the flexible structure is conducive to reinforcing load-lifting capacity, power efficiency and wing propulsion efficiency (Mountcastle and Combes, 2013;Liu et al, 2013;Zhu, 2007), and deformations of insect wings bring about a camber effect that may regulate the magnitude of lift and drag ratio and control the alteration of aerodynamic forces Zhao et al, 2010). Therefore, we believe that resilin, largely by determining the flexibility of the wings, is a principal reason why the honeybee and even insects in general are able to excellently perform flapping flight.…”
Section: Functional Role Of Resilin Patches In Wingsmentioning
confidence: 99%
“…Compared with a traditional NACA0012 airfoil, an optimal airfoil shape increased the output power and efficiency by 6%. More recently, an investigation into the effects of flexible flapping wings on power generation was conducted by Liu et al [18]. A similar study on the flexible airfoil effects can also be fond in the work by Hoke et al [19].…”
Section: Introductionmentioning
confidence: 95%